Uma cartografia do filme brasileiro em Nova Iorque (2003 a 2016): uma análise crítica - Borges, Marcia de Castro (2017)
This dissertation reflects on the cartography of the Brazilian film in New York from 2003 to 2016, based on a mapping of the exhibiting circuit of Brazilian films in the period, investigating the process of exhibition of these films. The contours and crosses in this cartography are defined through the interrelations present in this exhibiting circuit, expressed in its specificities, to understand its limits and its possibilities. The research was based on direct observation and data collection in archives related to the exhibiting circuit in New York City: Museum of Contemporary Art in New York (MoMA), Film Society of Lincon Center (FSLC), Brazilian Film Festival of New York (BRAFF-NY), and Museum of the Moving Image. (MoMI), The New York Times (NYT) and Film Comment (FC). Considering the data present in the archives, in its circumstantial aspects, hidden and polyphonic, in the constitution of the cartographic process, we seek to perceive its regularities and deviations, and also to notice how these films are seen in the critical reviews published in the press about them. The visibility of Brazilian films in New York, goes beyond the circularity that they configure, in that way they arouse several glances - present in the critical reviews - on the Brazilian cultural imaginary.